2016
DOI: 10.1016/s2213-8587(16)00044-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal gestational vitamin D supplementation and offspring bone health (MAVIDOS): a multicentre, double-blind, randomised placebo-controlled trial

Abstract: Arthritis Research UK, Medical Research Council, Bupa Foundation, and National Institute for Health Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
212
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(235 citation statements)
references
References 37 publications
9
212
3
4
Order By: Relevance
“…There is increasing evidence that the early life environment has effects on acquisition of peak bone mass, and that poor growth in early life is associated with reduced bone mass at peak and in old age [40], and with increased risk of hip fracture [41]. The specific environmental influences that might underlie these associations are beginning to be characterised and include factors such as maternal diet, lifestyle and physical activity during pregnancy [42], and maternal gestational 25(OH)-vitamin D concentrations [43,44]. Finally, it is possible that changes in clinical practice may have influenced the ascertainment and reporting of certain fracture types: For example, rib fractures in the UK are now rarely the subject of radiographic confirmation; in contrast, there has been a great deal of effort internationally to increase awareness of vertebral fractures, both clinically and radiographically [45].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that the early life environment has effects on acquisition of peak bone mass, and that poor growth in early life is associated with reduced bone mass at peak and in old age [40], and with increased risk of hip fracture [41]. The specific environmental influences that might underlie these associations are beginning to be characterised and include factors such as maternal diet, lifestyle and physical activity during pregnancy [42], and maternal gestational 25(OH)-vitamin D concentrations [43,44]. Finally, it is possible that changes in clinical practice may have influenced the ascertainment and reporting of certain fracture types: For example, rib fractures in the UK are now rarely the subject of radiographic confirmation; in contrast, there has been a great deal of effort internationally to increase awareness of vertebral fractures, both clinically and radiographically [45].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, Cooper and Harvey and co-workers (199,200) provided preliminary results of the MAVIDOS study from the United Kingdom. The 900 women who completed the study randomly received either 1,000 IU vitamin D or placebo beginning at 14 wk of pregnancy.…”
Section: Yu Etmentioning
confidence: 99%
“…Baseline 25OHD was ϳ45 nM (18 ng/ml), did not change in placebo-treated women, and rose to 68 nM (27 ng/ml) near term in the vitamin D-supplemented women. During the oral and poster presentation of results (199,200), the study was revealed to be negative in its primary outcome (neonatal bone area, bone mineral content, and bone mineral density within the first 14 days after birth) and secondary outcome 23), suggested a possible benefit on bone mineral content of winter-born babies. If the apparent benefit on winter-born babies is real and not a chance result, it may not be an indication of an effect on the fetus but instead a postnatal effect, since (as noted earlier) the neonatal skeleton should gain 100 mg calcium per day over the first 14 days after birth.…”
Section: Yu Etmentioning
confidence: 99%
“…The provided daily dose of supplemental vitamin D goes in hand with that previously documented in literature; where Cooper et al, (2016) found supplementation of women with cholecalciferol 1000 IU/day during pregnancy is sufficient to ensure that most pregnant women are vitamin D replete, and it is safe. Ceccaldi et al, (2017) documented that despite national guidelines on vitamin D supplementation, the rates are currently insufficient and the recommended 100,000 IU single dose helps to limit deficiency in newborns, but it fails to cover infant's needs for optimal status.…”
mentioning
confidence: 86%